2018
DOI: 10.23736/s1973-9087.17.04680-9
|View full text |Cite
|
Sign up to set email alerts
|

Active exergames to improve cognitive functioning in neurological disabilities: a systematic review and meta-analysis

Abstract: The final version may contain major or minor changes.Subscription: Information about subscribing to Minerva Medica journals is online at: http://www.minervamedica.it/en/how-to-order-journals.php Reprints and permissions: For information about reprints and permissions send an email to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(67 citation statements)
references
References 53 publications
7
56
0
4
Order By: Relevance
“…88,89 Compared to traditional rehabilitation approaches, exergame-based interventions (which are considered nonimmersive VR systems) were found to improve to a significantly greater extent executive functions and visuospatial perception in adult populations with neurological disabilities and in children with neurodevelopmental disorders. 90 Nevertheless, the effect of nonimmersive VR neurorehabilitation training on HRQoL has so far not been well debated, due to few, low-quality studies of the evidence also confirmed by our findings. 86 Indeed, two meta-analyses on VR-based interventions for specific neurologic disorders reported similar effects on HRQoL for VR and conventional physiotherapy in individuals with Parkinson's disease, 91 together with a lack of scientific evidence for VR-based interventions on HRQoL in poststroke survivors.…”
Section: Discussionsupporting
confidence: 65%
“…88,89 Compared to traditional rehabilitation approaches, exergame-based interventions (which are considered nonimmersive VR systems) were found to improve to a significantly greater extent executive functions and visuospatial perception in adult populations with neurological disabilities and in children with neurodevelopmental disorders. 90 Nevertheless, the effect of nonimmersive VR neurorehabilitation training on HRQoL has so far not been well debated, due to few, low-quality studies of the evidence also confirmed by our findings. 86 Indeed, two meta-analyses on VR-based interventions for specific neurologic disorders reported similar effects on HRQoL for VR and conventional physiotherapy in individuals with Parkinson's disease, 91 together with a lack of scientific evidence for VR-based interventions on HRQoL in poststroke survivors.…”
Section: Discussionsupporting
confidence: 65%
“…Interviews showed a strong acceptance of the exergames by patients (even in the first study). The majority would welcome the integration of exergames into their conventional therapy because of their appealing nature and beneficial motor-cognitive training approach [40,106]. The combined training regimen allows for the concurrent processing and synchronization of cognitive and motor stimuli and therefore can trigger brain-body communication.…”
Section: Exergame As An Ms Therapy Toolmentioning
confidence: 99%
“…In recent years, researchers have started to evaluate exergames as a rehabilitation tool for patients with MS. Exergames proved to be an acceptable, feasible, safe, enjoyable, challenging, and self-motivating tool [38][39][40]. Kramer et al [41] concluded that the integration of exergames seemed to have a positive effect on training adherence and therefore could support the efficacy of long-term rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exergames, which require physical effort and are controlled by (whole) body movements ( Oh and Yang, 2010 ), have been promoted as suitable tools for providing attractive and effective training alternatives or supplements by the interdisciplinary research and development (R&D) community. In more than 10 years, R&D work has proved that exergames have the potential to be training tools that are both effective (i.e., increasing physical-cognitive fitness, endurance, strength, and coordination) ( Staiano and Calvert, 2011a , b ; Sween et al, 2014 ; Best, 2015 ; Benzing et al, 2016 ; Kari, 2017 ; Mura et al, 2018 ; Stojan and Voelcker-Rehage, 2019 ; Xiong et al, 2019 ) and attractive (e.g., increasing training adherence, motivation, flow, and engagement) ( McRae et al, 2012 ; Valenzuela et al, 2018 ; Martin-Niedecken et al, 2019b ; Tondello et al, 2019 ). Furthremore, exergamging promotes physical activity and training in different target populations ( Lu et al, 2013 ; Kappen et al, 2019 ; Martin-Niedecken and Schättin, 2020 ).…”
Section: Introductionmentioning
confidence: 99%